Prototype Design and Development of an IoT-Enabled Monitoring and Control System for Public Street Lighting - Ilham, Dirja Nur; Candra, Rudi Arif; Budiansyah, Arie; Zulfan, Zulfan (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
This research discusses the Internet of Things (IoT)-based Public Street Lighting (PJU) system to improve energy efficiency and remote monitoring. The background problem is the need to improve operational efficiency and energy savings in the PJU system. This final project aims to design and test an IoT-based PJU system that transmits real-time data between nodes and gateways using LoRa technology and the MQTT protocol. The research process involves hardware and software design, as well as system testing under various conditions. The tests measured the data transmission time and analyzed the delay using LED indicators on the gateway and dashboard devices. The test results showed significant variations in data transmission time compared to the programmed time. The programmed transmission time was 10 seconds for node 1 and 20 seconds for node 2, but the test results showed an average time of about 15 seconds for node 1 and 21.89 to 36.02 seconds for node 2. This variation is due to factors such as network communication delay, processor load, and LoRa system efficiency.